Relationship between distributed leadership and self-efficacy of catechists in catechetical schools within the Archdiocese of Kuala Lumpur - Lazaroo, Brian Jude; Omar, Muhd Khaizer (Human Resource Management Academic Research Society, 2024)
This study delved into determining the relationship between distributed leadership, characterised by collaborative decision-making, supportive supervision, coherent practices, and catechist self-efficacy within catechetical schools of the Archdiocese of Kuala Lumpur. Surveying 260 catechists, the study revealed a landscape of moderate perceptions of leadership support and practices alongside generally positive yet nuanced self-efficacy levels indicating individual variations. However, the spotlight shone brightest on the Pearson correlation analyses, unveiling remarkably strong positive correlations between all three leadership dimensions and self-efficacy (r = .993, .987, and .990, respectively). This potent connection illuminates a powerful truth: distributed leadership, when woven into the fabric of catechetical schools through collaboration and supportive supervision, serves as a potent catalyst for igniting catechist confidence and unlocking their effectiveness. This revelation compels us to advocate for strategic investment in leadership development programs that invigorate distributed leadership practices, particularly in the domain of supervision. By empowering catechists through such interventions, the potential to optimise catechetical education and nurture stronger faith formation within the Archdiocese becomes not just a possibility but a compelling reality.